Preventive Effect of Syringic acid on Hepatic Marker Enzymes and Lipid Profile Against Acetaminophen-Induced Hepatotoxicity Rats - Raja, Boobalan (International Journal of Pharmaceutical & Biological Archive, 2010)
Syringic acid is a phenolic that exists in nature and is the major component of some traditional medicinal herbs. We investigated the hepatoprotective and antihyperlipidaemic potential of syringic acid against acetaminophen (APAP) (a single intraperitoneal injection 750 mg/kg BW) induced hepatotoxicity in male albino Wistar rats. APAP rats inhibited increased liver marker enzyme activities aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and gamma-glutamyl transpeptidase levels and lipid profile. Rats when treated with syringic acid at different concentrations (25, 50 and 100 mg/kg BW, p.o.) caused a significant decreased serum marker enzyme activities. It also decreased the levels of very low density lipoprotein cholesterol (VLDL-C) and low density lipoprotein cholesterol (LDL-C) while high density lipoprotein cholesterol (HDL-C) phospholipids significantly increased. It also decreased the levels of total cholesterol, triglycerides, phospholipids and free fatty acids in the plasma and tissues of liver and kidney. The activity of syringic acid (50 mg/kg) is comparable with silymarin, a known hepatoprotective drug. Syringic acid, thus exhibits hepatoprotective and antihyperlipidemic activity.